Mission paw - Guerdat, Andy; Lovett, Nate; Sullivan, Steve (Steven); Nickelodeon (Firm); Spin Master (Firm) (New York Random House, 2017)
Chase and his PAW patrol friends come to the rescue when the royal crown of Barkingburg is stolen
"Based on the teleplay "Mission paw" by Steve Sullivan and Andy Guerdat."
At head of title: Nickelodeon Paw Patrol
Keywords: Dogs -- Fiction; Rescue work -- Fiction; Crowns -- Juvenile fiction; Dogs -- Juvenile fiction; Rescue work -- Juvenile fiction; Crowns -- Fiction